Coccidiosis In Broiler Chicken Aged 27 Days From A Farm In Tunjuk, Marga, Tabanan, Bali: A Case Study - Amelia, Ni Kadek Shita; Suratma, Nyoman Adi; Berata, I Ketut; Besung, I Nengah Kerta; Mahardika, I Gusti Ngurah Kade (Jurnal Medika Veterinaria, 2025)
Coccidiosis, also commonly referred to as bloody diarrhea, is caused by Eimeria spp. and primarily affects the digestive tract. The most pathogenic Eimeria species in chickens are Eimeria tenella and Eimeria necatrix. The subject of this case study was a 27-day-old female broiler chicken from a commercial farm located in Tunjuk Village, Marga Subdistrict, Tabanan Regency, Bali. The chicken had been reported to suffer from bloody diarrhea for five days, accompanied by clinical signs of weakness, anorexia, pale comb, ruffled feathers, and a tendency to huddle in the corner of the pen. This case study aimed to describe the anatomical pathology, histopathology, and laboratory findings to obtain a definitive diagnosis of the disease affecting this chicken. The results of the anatomical pathology examination showed hemorrhage in the cecum. Histopathological examination of the cecum revealed the presence of schizonts, hemorrhage, and inflammatory cell infiltration. Qualitative fecal examination confirmed the presence of Eimeria spp. oocysts, while quantitative fecal examination using the McMaster technique revealed 895,600 oocysts per gram of feces, indicating a severe infection. Based on clinical observations, epidemiological data, gross pathological changes, histopathological findings, and fecal examinations using native, sedimentation, flotation, and McMaster methods, it was concluded that the chicken was affected by coccidiosis.